Jüdische Identität in Deutschland und im Exil : Der Lebensweg des Wissenschaftlerehepaars Hans und Rahel Liebeschütz - Kaiser, Silke 1964- (Hamburger Historische Forschungen, 2023)
Hans and Rahel Liebeschütz were a German-Jewish scientific couple. Both grew up in Hamburg during the German Empire and began their scientific careers in the Weimar Republic. Rahel Liebeschütz was the first woman to habilitate at the Medical Faculty of the University of Hamburg. Hans Liebeschütz was a historian and habilitated in Medieval Latin philology in 1929. The transfer of power to the National Socialists meant the end of their academic careers. Nevertheless, they remained in Hamburg until 1938 and experienced with their three children the increasing disenfranchisement of Jews. It was not until 1938/1939 that they emigrated to England, where they remained after the end of the war. Their impressive career and difficult life in the "Third Reich" and in exile are traced from archival and personal sources. In the second edition of the biography, the author has incorporated new publications as well as previously unknown sources